Zooplankton structure and dynamics in two estuaries from the Atlantic coast in relation to multi-stressors exposure. (20th December 2015) - Vieira, L.R.; Guilhermino, L.; Morgado, F.
Abstract: The aim of this research was to investigate the response of pelagic zooplankton to different levels of abiotic multi-stressors in the North Atlantic coast, taking advantage of the comparison of the communities of two adjacent estuaries with different levels of historical pollution (estuaries of Minho and Lima Rivers). The zooplankton community structure, composition and temporal variation were comparatively investigated for 15 months, using different net meshes. Several abiotic factors were measured in situ and water samples were simultaneously collected for determination of nutrients and chlorophyll a . The overall results revealed a diverse community represented by species that have been found in subtropical and temperate zones. Although the highest diversity was observed in the Lima estuary, supported by higher contributions of marine taxa, the total zooplankton biomass was found to be significantly higher in the Minho estuary. The salinity gradient differences between estuaries, associated to significant differences in water nutrients levels, were found to be the main forcing factors affecting micro and mesozooplankton. Considering the importance of the impacts resulting from abiotic variation on the basis of aquatic food webs, the present investigation represented a case-study, based in two contrasting estuaries, one strongly influenced by freshwater discharges (Minho estuary) and the other with higher salinity levels (Lima estuary), contributing to a better understanding of the effects of multi-stressors on pelagic zooplankton communities, providing useful information for studies related with climate change impacts, biogeography, conservation and providing data contributing to the improvement of pelagic fisheries management models. Graphical abstract: Highlights: Despite the Iberian NW coast importance, few studies have investigated the zooplankton communities. We studied the zooplankton structure and dynamics in 2 estuaries in relation to multi-stressors. The results revealed significant differences in diversity and total abundances. Salinity and water quality were the main forcing factors affecting the zooplankton community. This work represents a case study contributing for coastal management and modelling.